Adesão a crenças cristãs normativas sobre a sexualidade : um estudo com jovens evangélicos de João Pessoa, PB. - Monteiro, Robinson Grangeiro (2011)
The two-fold subject of Religiosity and Sexuality encompass aspects tha have been studied separately by various approaches and different authors. The Psychology of Religion, since the creation of 36th Division at American Psychology Association and with the publication of many books, studies and researches (Emmons 1999; Hill & Hood 1999; Koenig 1998; Miller 1999; Pargament 1997; Richards & Bergin 1997, 2000; Shafranske 1996) has focused the religious universe as regulatory instance over sexuality interacting to other discourses (Citelli, 2005; Cunha, 2000; Heilborn, 2006; 1991; Gonçalves da Silva et al, 2008). However, still remains, specially in Brazil, a lack of studies and researches under Psychology field, that deal with this two-fold subject - Religiosity and Sexuality regarding to individual adherence to Christian normative group beliefs about Sexuality (heterosexuality, chastity and conjugal fidelity). From Social Identity Theory (SIT) by Tajfel e Turner (1979; 1981; 1983), the most important theory about intergroup relations in Social Psycholoy (Amâncio, 1993) and structured in three concept ( social categorization, social identity and social comparison), and also, taking studies on Group Beliefs, this present work has as Main Objective: to analyze some of the psychosocial phenomena that influence the evangelical youth people adherence to Christian normative group beliefs about Sexuality. Its Specific Objectives are to describe the judgment of seriousness of anti-normative sexual behaviors, tolerance to interreligious affective relationships, the sense of belonging to the churches that they attend by young evangelical people, the evaluation of the importance of this belongingness, the evaluation about spiritual proximity to other evangelicals, the participation in church activities, the experience of dating relationships and analysis of relations about those variables, including the ones that best predict the adherence to beliefs. The samples is not randomized chosen by convenience (Mattar, 2001; Cozby, 2003) taking 429 participants, both sex, ages between 17 to 30 years old, attendees to evangelical churches of João Pessoa, Paraíba state, Brazil, present on time when the data were collected and free willing to participate. The Instrument has demographics (age, sex, educational level, family income), besides other elements as the experience of dating relationships (type and how many relationships), religious identity (the sense of belonging to the churches that they attend by young evangelical people, the evaluation of the importance of this belongingness, the evaluation about spiritual proximity to other evangelicals Historical Evangelicals, Pentecostals and Neo Pentecostals), the participation in church activities and adherence to Christian Normative Group Beliefs about Sexuality (the judgment of seriousness of anti-normative sexual behaviors and the tolerance to interreligious affective relationships). Study Procedures: a pilot test was applied in two different occasions to 30 youth people of Presbyterian Church of Tambaú (João Pessoa, PB) to verify the clarity and adequacy of the instrument items and the participants reaction. The results were excluded from the final results. The data collect itself was made between November, 2010 and March, 2011 in events, meeting, including spiritual retreats and camps of 10 evangelical churches of João Pessoa, Paraíba state, according to religious institutions legal authorities´ permission. Output: from an Exploratory Factor Analysis (EFA) by Principal component analysis (PCA) fixing a Factor (KMO (0,922), Bartlett test of sphericity [χ2 (91) = 7476,560 p < 0,001], 67,3 % of variance, Cronbach´s Alpha (α = 0,96), Eigenvalue (9,426), Mean (8,5) and standard deviation (2,4), the output indicates that items with homosexuality content present heavier factor loading regarding to latent variables, the items with contents implying adultery or infidelity, identifying interpersonal relations, came out as the second group with heavier factor loading regarding to latent variables, while the items included in more private and personal behaviors present the lightest contribution to the constitution of latent variables. The Tolerance to Interreligious Affective Relationsthips indicator with Mean (1,7) and Stantard Deviation (2,30) was built, indicating strong rejection to Interreligious Affective Relationsthips by participants in the sample, especially in regarding to participants of afrobrazilians religious (candomblé and umbanda). The results also express a strongly identified to the its group sample by its Sense of Belongingness (Mean 8,4 and Standard Deviaton 2,24) and by the Evaluation of the Importance of this Belongingness (Mean 9,2 and Standard Deviation 1,76). The Spiritual Proximity with other Evangelicals has (Mean 2,2 and Standard Deviation 0,86), confirming the hypothesis. The results related to the Participation in Churches Activities present Mean 17,3 and Standard Deviation 5,0 with high level of participation, especially in those activities that characterize stronger commitment to the local church. The Dating Relationships Mean is 2,2 and Standard Deviation 1,92, confirming the conservative profile of the sample. The Variables Correlation shows that variables indicating adherence to Christian Normative Group Beliefs about Sexuality (the judgment of seriousness of anti-normative sexual behaviors and the tolerance to interreligious affective relationships) are negatively correlated with weak intensity. The variables related to Religious Social Identity (the sense of belonging to the churches that they attend by young evangelical people, the evaluation of the importance of this belongingness, the evaluation about spiritual proximity to other evangelicals) are positively correlated from weak to moderate intensity. The variables participation in churches activities and experience with dating relationships has not association. Notice that, regarding to participation in churches activities, there is a positive relation, yet still weak, to every one of those Religious Social Identity variables, indicating that a more effective participation in church activities is associated to a stronger Religious Social Identity. Nevertheless, the intensity of this association is weak as well. In relation to Experience to Dating Relationships (number of dating relationships), the output shows it negatively and weakly related to the Spiritual Proximity to Other Evangelicals. This can be considered as accidental output, since there is no reason to think that relation has anything to Religious Social Identity. The results of Regression Multiple (stepwise method R2 (ajustado) = 0,07 (7%) F (3/346) = 9,085; P < ,0001) indicates that the variable that contributes most to Adherence to Christian normative group beliefs about Sexuality, defined by the judgment of seriousness of anti-normative sexual behaviors, is the Importance of Belongingness (β = 0,15), followed by the Sense of Belongingness (β = 0,13), both related positively to the criteria variable; the Number of Dating Relationships (β = - 0,12) also contributes, but negatively. The Participation in Churches Activities and the Spiritual Proximity to other Evangelicals do not play any important role related to the judgment of seriousness of anti-normative sexual behaviors. Noticeable too is that the model tested explains only 7 % of the variance of that variable. The results of Regression Multiple (stepwise method R2 (ajustado) = 0,13 (13%) F (3/346) = 19,391; P < ,0001) indicates that the variable that contributes most to Adherence to Christian normative group beliefs about Sexuality, defined by the Tolerance to Interreligious Affective Relationships, is the Sense of Belongingness (β = - 0,20), followed by the Importance of the Belongingness (β = - 0,15), and Participation in Churches Activities (β = - 0,13), all related negatively to the criteria variable. The variables Number of Dating Relationships and Spiritual Proximity to other Evangelicals do not play any important role in regarding to the Tolerance to Interreligious Affective Relationships. The tested model explains only 13% of the variable variance.